2006
DOI: 10.1529/biophysj.105.080606
|View full text |Cite
|
Sign up to set email alerts
|

Probing Single-Cell Micromechanics In Vivo: The Microrheology of C. elegans Developing Embryos

Abstract: Cells are not directly accessible in vivo and therefore their mechanical properties cannot be measured by methods that require a direct contact between probe and cell. Here, we introduce a novel in vivo assay based on particle tracking microrheology whereby the extent and time-lag dependence of the mean squared displacements of thermally excited nanoparticles embedded within the cytoplasm of developing embryos reflect local viscoelastic properties. As a proof of principle, we probe local viscoelastic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
151
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 41 publications
15
151
0
2
Order By: Relevance
“…These results indicate that a Newtonian fluid is a good approximation and thus, nonNewtonian properties appear to play a minor role in cytoplasmic streaming in C. elegans. This finding is consistent with a previous microrheology study showing that simple diffusion was observed in the cytoplasm of the C. elegans embryo (35). Although nonNewtonian properties may appear when much larger or smaller forces are applied, the cytoplasm of the C. elegans embryo appears to behave as a Newtonian fluid under physiologically relevant amplitudes of applied force.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that a Newtonian fluid is a good approximation and thus, nonNewtonian properties appear to play a minor role in cytoplasmic streaming in C. elegans. This finding is consistent with a previous microrheology study showing that simple diffusion was observed in the cytoplasm of the C. elegans embryo (35). Although nonNewtonian properties may appear when much larger or smaller forces are applied, the cytoplasm of the C. elegans embryo appears to behave as a Newtonian fluid under physiologically relevant amplitudes of applied force.…”
Section: Discussionsupporting
confidence: 92%
“…The viscosity associated with the observed damping is, thus, on the order of 1 Pa·s, which is consistent with our previous measurements of cytosol viscosity using beads. This value is also consistent with microrheological measurements made in the cytosol of Caenorhabditis elegans embryo (19).…”
Section: Significancesupporting
confidence: 91%
“…Single cells can be manipulated to probe the strength and location of receptor binding 16 and adhesion or to measure traction and adhesion forces 17 . Viscoelastic properties can be measured on short length-scales and in small volumes 18 , such as within cells 19 . Early applications of single-molecule force and displacement measurements included the characterization of conventional motor proteins such as kinesins 20,21 and myosins 22 .…”
Section: Introductionmentioning
confidence: 99%